Social and institutional factors affecting sustainability innovation in universities: A computer re-use perspective. (20th June 2019) - Wang, Charlotte; Alvarez-Gaitan, Juan Pablo; Moore, Stephen; Stuetz, Richard
Abstract: With the wave of digitisation sweeping through the higher education sector, end-of-life outcomes for decommissioned computers will pose a serious sustainability challenge for higher education institutions. This challenge presents an opportunity for universities to implement and demonstrate best practice in sustainability; in this case, computer re-use schemes. The paper addresses the practical realisation of sustainability innovation in a social and institutional context via an examination of the first computer re-use scheme implemented within an Australian university. It also contributes a unique, institutional and social perspective to the study of a sustainability innovation, computer re-use schemes. The key factors that contributed to the successful implementation of the Scheme are derived and presented as a social and institutional model for implementing sustainability initiatives. A summary of the model is presented in the graphical abstract. Given the complex organisational structure of universities, these learnings can be relevant to a wide range of institutions and the implementation of other sustainability initiatives. Graphical abstract: Image 1 Highlights: A social and institutional model for sustainability innovation is presented. Student leadership and initiative was the catalyst for the re-use scheme. A common language and stated objective for sustainability and social impact supported the scheme. Partnerships led to new organisational and delivery set-ups for sustainability innovation.